I precetti noachidi secondo Maimonide tra Torà e legge naturale nella rivisitazione di alcuni maestri contemporanei (Doctor Virtualis, 2022)
The essay presents Maimonides’ definition and interpretation of the seven Noahide laws as they are found in the halakhic code Mishnè Torà, Hilkhot melakhim, and as discussed and elaborated by the contemporary Jewish (German-American) thinker Steven S. Schwarzschild. In comparison with other rabbinical versions, Maimonides’ interpretation adds the condition that the observance of those laws is valid only if they are accepted and obeyed as revealed laws, not only as lex naturalis. About such a condition a disagreement exists among the Jewish scholars and rabbis, for example between Marvin Fox and Aaron Lichtenstein (their position is a case-study presented here). More deeply, Schwarzschild argues in favor of the Rambam’s interpretation and tries to demonstrate that it is consistent with the comprehensive vision Maimonides had on Judaism as such.
Keywords: Maimonide; Schwarzschild; Natural Law; Revelated Law